Printing Change, Changing Print: Macleod, Kirsten, American Little Magazines of the Fin de Siècle: Art, Protest, and Cultural Transformation, Toronto: University of Toronto Press, 2018 - Ritchie, Jay (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2026)
The review examines the contributions of Kirsten MacLeod’s American Little Magazines of the Fin de Siècle: Art, Protest, and Cultural Transformation (2018) to the fields of bibliographical studies and American literature. The role of little magazines in consolidating the interests and ideological position of an emergent professional-managerial class in the United States is presented as the book’s central thesis. Insights into the affective register of fin-de-siècle little magazines are highlighted, which are bolstered by the author’s comprehensive survey of the material. The review accentuates the judiciousness with which the author asserts her claims: rather than insist on the revolutionary nature of little magazines, MacLeod establishes how social progress was encouraged by a class of people invested in maintaining their position in society. Pointing out potential applications of MacLeod’s study to scholars of contemporary print culture, the review also highlights the author’s analysis of the relationship between other types of self-publishing and cultural formation.